Building Cisco Networks For Windows 2000 - Lewis, Elliot (Syngress Media, 2011)
Microsoft Corporation, the world's largest software vendor, and Cisco Systems, the world's largest internetworking vendor, have jointly developed a common software interface for managing Cisco hardware on Microsoft networks: Cisco Network Services for Active Directory (CNS/AD). Until now, network administrators have been forced to master two completely different product interfaces to effectively manage their networks. Configuring Cisco Network Services for Active Directory is the first book announced for this enormous Information Technology audience.